The Prophetic Approach to Enhance Confidence: An Analytical Study - Alasasmeh , Adel Harb Bashir (Dirasat: Shari’a and Law Sciences, 2020)
The study aims to identify the prophetic methods in dealing with his companions. The Prophet (PBUH) applied theories that would compensate and compensate the risk, alleviate the pain and comfort the injured, and urge the initiator to take out his activities, which is an applied scientific approach and not a theoretical approach truncated from reality. The study used the inductive method to extrapolate the means of enhancing confidence from the Prophet (PBUH) to the parish; it addressed it with special headings under which the names of reinforcement fall and mentioned under each heading a range of hadiths of Al-Mustafa (PBUH) that fit an educational curriculum and Islamic tradition for such studies. The study found that the approach of prophetic reinforcement is a sober approach, enriches the soul and develops a sense of useful work, encourages creativity, and creates ambition and excellence, and it is a practical applied approach and was not only theoretical, the reinforcement is divided into positive and negative; just as encouragement and motivation are towards serious action and good work, there is negative reinforcement through aversion from evil deeds, vilification of bad work, committing sins, and distance from Haram. The study recommends the importance of applying the prophetic approach in all other studies, and not only on the educational or educational side, but on the psychological, emotional and spiritual side.